La riforma della Politica Agricola Comunitaria e la filiera olivicolo-olearia italiana - Casini, Leonardo (Strumenti per la didattica e la ricerca, 2003)
The book illustrates the results of a wide-ranging survey of the overall situation of the olive oil market and the Italian production chain for olives and olive oil. Based on the results of this investigation, two possible prospects for development have been identified. The first follows the guidelines that prevail at Community level, favouring a specialist olive cultivation. The second instead aims at a valorisation of agriculture where it features social aspects of particular significance. From this viewpoint the various olive farms in Italy ought not to be considered in a standardised manner, but individually valorised in relation to their different functions, which are not necessarily expressed in terms of yield.